Role of Farnesoid X Receptor and Bile Acids in Hepatic Tumor Development. Issue 12 (1st October 2018) - Takahashi, Shogo; Tanaka, Naoki; Fukami, Tatsuki; Xie, Cen; Yagai, Tomoki; Kim, Donghwan; Velenosi, Thomas J.; Yan, Tingting; Krausz, Kristopher W.; Levi, Moshe; Gonzalez, Frank J.
Abstract : Hepatocellular carcinoma (HCC) is a leading cause of cancer deaths worldwide, and an association between altered bile acid (BA) metabolism, down‐regulation of farnesoid X receptor (FXR), which is a master regulator of BA metabolism, and hepatocarcinogenesis has been documented. While global FXR deficiency in mice results in spontaneous HCC with aging, the contribution of tissue‐specific FXR deficiency to hepatocarcinogenesis remains unclear. In this study, the prevalence of hepatic tumors, expression of genes related to tumorigenesis, and serum/liver BA levels were compared among male whole‐body Fxr ‐null, hepatocyte‐specific Fxr ‐null ( Fxr ∆Hep ), and enterocyte‐specific Fxr ‐null ( Fxr ∆IE ) mice at the age of 3, 14, and 20 months. More than 90% of 20‐month‐old whole‐body Fxr ‐null mice had hepatic tumors with enhanced hepatic expression of myelocytomatosis oncogene ( Myc ) and cyclin‐dependent kinase 4 ( Cdk4 ) messenger RNAs (mRNAs) and elevated serum taurocholate (TCA) and tauromuricholate (TMCA) and their respective unconjugated derivatives. The incidence of hepatic tumors was significantly lower in Fxr ∆Hep and Fxr ∆IE mice (20% and 5%, respectively), and the increases in Myc and Cdk4 mRNA or serum BA concentrations were not detected in these mice compared to Fxr floxed [fl]/fl mice; a similar tendency was observed in 14‐month‐old mice. However, increased hepatic c‐Myc protein expression was found only in Fxr ‐null mice at the age of 3, 14, and 20 months. Treatment with TCA induced Myc expression in Fxr ‐null cultured primary mouse hepatocytes but not in wild‐type (WT) mouse hepatocytes, demonstrating that the combination of hepatocyte FXR disruption with elevated TCA is required for Myc induction and ensuing age‐dependent hepatocarcinogenesis in Fxr ‐null mice. Conclusion : There is a relatively low risk of hepatic tumors by inhibition of FXR in enterocytes, likely due to the lack of increased TCA and Myc induction. Abstract : A combination of FXR disruption in liver and intestine results in elevated taurocholic acid TCA) and Myc induction, resulting in age‐dependent hepatocarcinogenesis in farnesoid X receptor deficient mice. This study reveals relatively a low incidence of hepatic tumors by FXR deficiency in either hepatocytes or enterocytes alone, likely due to the lack of increased TCA. These findings provide novel insights into the tight association between disruption of BA metabolism, FXR signaling, Myc overexpression, and hepatic tumorigenesis.